3D printing towards implementing Industry 4.0: sustainability aspects, barriers and challenges. Issue 3 (18th January 2022) - Malik, Abrar; Ul Haq, Mir Irfan; Raina, Ankush; Gupta, Kapil
Abstract : Purpose: Environmental degradation has emerged as one of the major limitations of industrial revolution and has led to an increased focus towards developing sustainable strategies and techniques. This paper aims to highlight the sustainability aspects of three-dimensional (3D) printing technology that helps towards a better implementation of Industry 4.0. It also aims to provide a brief picture of relationships between 3D printing, Industry 4.0 and sustainability. The major goal is to facilitate the researchers, scholars, engineers and recommend further research, development and innovations in the field. Design/methodology/approach: The various enabling factors for implementation of Industry 4.0 are discussed in detail. Some barriers to incorporation of 3D Printing, its applications areas and global market scenario are also discussed. A through literature review has been done to study the detailed relationships between 3D printing, Industry 4.0 and sustainability. Findings: The technological benefits of 3D printing are many such as weight savings, waste minimization and energy savings. Further, the production of new 3D printable materials with improved features helps in reducing the wastage of material during the process. 3D printing if used at a large scale would help industries to implement the concept of Industry 4.0. Originality/value: This paper focuses on discussing technological revolution under Industry 4.0 and incorporates 3D printing-type technologies that largely change the product manufacturing scenario. The interrelationships between 3D printing, Industry 4.0 and sustainability have been discussed.